Resveratrol Alleviates Levodopa-Induced Dyskinesia in Rats - Zheng, Chang-Qing; Fan, Hong-Xia; Li, Xiao-Xian; Li, Jing-Jie; Sheng, Shuo; Zhang, Feng (Frontiers in Immunology, 2021)
Dyskinesia is a serious complication of Parkinson's disease during levodopa (L-DOPA) treatment. The pathophysiology of L-DOPA-induced dyskinesia (LID) is complex and not fully illuminated. At present, treatment of dyskinesia is quite limited. Recent studies demonstrated neuroinflammation plays an important role in development of LID. Thus, inhibition of neuroinflammation might open a new avenue for LID treatment. Resveratrol (RES) is the most well-known polyphenolic stilbenoid and verified to possess a large variety of biological activities. DA neurotoxicity was assessed via behavior test and DA neuronal quantification. The movement disorders of dyskinesia were detected by the abnormal involuntary movements scores analysis. Effects of RES on glial cells-elicited neuroinflammation were also explored. Data showed that RES attenuated dyskinesia induced by L-DOPA without affecting L-DOPA’s anti-parkinsonian effects. Furthermore, RES generated neuroprotection against long term treatment of L-DOPA-induced DA neuronal damage. Meanwhile, RES reduced protein expressions of dyskinesia molecular markers, ΔFOS B and ERK, in the striatum. Also, there was a strong negative correlation between DA system damage and ΔFOS B level in the striatum. In addition, RES inhibited microglia and astroglia activation in substantia nigra and subsequent inflammatory responses in the striatum during L-DOPA treatment. RES alleviates dyskinesia induced by L-DOPA and these beneficial effects are closely associated with protection against DA neuronal damage and inhibition of glial cells-mediated neuroinflammatory reactions.